Prospective study of safety, immunogenicity, and efficacy of inactivated COVID-19 vaccine in tuberous sclerosis complex children on sirolimus - Sufang Lin; Xia Zhao; Lin Li; Qiru Su; Weiwei Long; Xiaoqin Tian; Jinghua Ye; Bixia Yuan; Yan Hu; Jianxiang Liao; Hongbing Zhang (Human Vaccines & Immunotherapeutics)
While sirolimus is widely used in tuberous sclerosis complex (TSC), its impact on coronavirus disease 2019 (COVID-19) vaccination remains unclear. To evaluate the safety, immunogenicity, and efficacy of inactivated COVID-19 vaccine on the children with TSC on sirolimus, we conducted a prospective cohort study (July 1st, 2021–April 1st, 2022) in 117 children: 43 patients with sirolimus, 18 patients without sirolimus, and 56 healthy controls. Neutralizing antibody titers were measured pre-vaccination and at one and three months after the two-dose vaccination and adverse events were monitored throughout follow-up. Infection incidence was assessed via questionnaire. The primary endpoint was seroconversion rate, with secondary endpoints including neutralizing antibody titers, adverse events, and breakthrough infection incidence following China’s December 2022 COVID-19 surge. Results showed lower 1-month seroconversion (75.0% [12/16] vs 98.2% [55/56], p = .001) and reduced antibody titers (median 102.1 vs 213.1 IU/mL, p = .04) in non-sirolimus group versus controls, with declining trend in 3-month responses [44.4% (8/18) vs 54.5% (30/55), median 102.1 vs 213.1 IU/mL, p > .05]. Sirolimus group demonstrated stronger humoral responses versus non-sirolimus counterparts: higher antibody titers at 1 month (median: 168.9 IU/mL vs 102.1 IU/mL, p = .029) and 3 months (median: 38.1 IU/ml vs 15.8 IU/mL, p = .011), with higher seroconversion trend [1 month: 87.5% (35/40) vs 75% (12/16) (p = .259); 3 months: 67.6% (25/37) vs 44.4% (8/18)] (p = .1). The vaccine elicited attenuated immunogenicity in non-sirolimus group whereas vaccine combined with sirolimus might provide better protection against COVID-19. COVID-19 vaccination conferred good safety with mild breakthrough infections.